Relatório de Estágio Profissional "O Lugar do Professor de Educação Física do Século XXI "Estar onde os alunos estão"" - Vitor Hugo Leite Ribeiro (2019)
The current document prepared by me as a trainee student (author),recounts the experiences of my supervised practice, emphasizing myprofessional growth in favour of a culmination of a cycle of studies, which definesthe transition to the teaching profession. It documents my personal experiencelived during my supervised teaching, where many of the feelings present in thisjourney are reported, the main difficulties experienced, learnings from frustrationand anxiety. It also evidences the methodical and ambitious way in which thismanages to reconcile the whole process of supervised practice with this workbeyond the professional stage. This document was conceived in the course unitof the professional internship course within the second year of the master'sdegree in Teaching Physical Education in Basic and Secondary Education, in theFaculty of Sports of the University of Porto. This report is organised in sixchapters, in the first chapter there is the "Introduction", where the aims of thematerialisation of this document are presented. Chapter two deals with "PersonalDimension", where there is the presentation of all my journey until here. Chapterthree deals with "Institutional Framework", where I refer to all aspects thatcharacterise the place of the teaching practise. Chapter four "OperationalFramework" subdivides into three Areas. Area 1, "Organisation and Managementof the Teaching and Learning", Area 2 "Participation in School and Relationshipwith the Community", and finally Area 3, "Professional Development", deals withthe aspects which have contributed to my vocational training. In chapter five my"Research Study" is mirrored. Finally, in chapter six, "Conclusions and FuturePerspectives", the conclusions of all experiences lived throughout the year, aswell as a brief reflection, some of the future perspectives are also mentioned.